Perfect Partner Remembering Anton Dolin - Percival, John (Dance Books Ltd., Alton,Hampshire (UK), 2008)
Remembering Anton Dolin: stage name of Syney Francis Patrick Chippendall Healey-Kay -as Clive Barnes noted, his friends called him Pat but never Sid.